2007
DOI: 10.1007/s10549-007-9813-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in breast cancer biological characteristics between ethnic groups in New Zealand

Abstract: These data suggest differences in tumour biology related to ethnicity in the Auckland population and this has implications for breast cancer screening and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
1
13
2
Order By: Relevance
“…The incidence rate of breast cancer in the 25-44 year age group is higher for Pacific women compared to European/Other women, which may be due to the early cancer-promoting effect of pregnancy [75]. In New Zealand, Pacific women are more likely to be younger than European/Other women at diagnosis, present with more advanced disease [76] and have prognostic phenotypes [77], which are associated with worse disease-free and overall survival [78].…”
Section: Breastmentioning
confidence: 99%
“…The incidence rate of breast cancer in the 25-44 year age group is higher for Pacific women compared to European/Other women, which may be due to the early cancer-promoting effect of pregnancy [75]. In New Zealand, Pacific women are more likely to be younger than European/Other women at diagnosis, present with more advanced disease [76] and have prognostic phenotypes [77], which are associated with worse disease-free and overall survival [78].…”
Section: Breastmentioning
confidence: 99%
“…Genetic risk factors for cancer among PIs have already been identified in polymorphism studies on a range of genes demonstrating ethnic differences in folate metabolism, nicotine metabolism, and estrogen biosynthesis (Feigelson et al, 2001; Kolonel, Altshuler, & Henderson, 2004; Le Marchand et al, 2004; Le Marchand, Haiman, Wilkens, Kolonel, & Henderson, 2004; Lea et al, 2005). PIs have also been found to have more aggressive tumorous cell growth in comparison to other racial/ethnic groups (Weston, Moss, Stewart, & Hill, 2008). Studies are needed to further understand phenotypic expressions resulting from gene and environment interplay; however, before such studies can be undertaken, we must first understand the cultural, psychological and sociological implications of such sample collection.…”
Section: Why a Special Issue On Cancer Disparities Among Pacific Islamentioning
confidence: 99%
“…There is a current concern about health disparities, especially cancer disparities, among different ethnic groups in New Zealand (1)(2)(3)(4)(5). The Maori people were early New Zealand settlers of Polynesian descent, who are considered the indigenous population of this country.…”
Section: Introductionmentioning
confidence: 99%
“…Immigration to New Zealand from the Pacific Islands is still common, and the most recent (2006) New Zealand census reported that 13% of the population selfidentified as Maori, whereas 6.0% self-identified as Pacific Islanders. Although, theoretically, the racial groups are well integrated, it has been observed that the Maori and Pacific Island people appear disadvantaged in most health statistics (1)(2)(3)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%